Inefficacy of neck cooling in suppressing core body temperature elevation during exercise in a hot environment: a randomized cross-over trial - Kotaro Ishizuka; Chikage Nagano; Mai Togawa; Kentaro Kado; Keiichi Tajima; Kimiyo Mori; Seichi Horie (Environmental Health and Preventive Medicine)
Background: Neck cooling is a practical method for preventing heat-related illness, however, its effectiveness in general workers is not well established. This study aimed to assess the effects of neck cooling on core body temperature and other physiological markers during exercise in a hot environment. Methods: This randomized crossover trial was conducted from November 2023 to April 2024 at the Shared-Use Research Center at UOEH. Fourteen healthy adult males participated in the study under two conditions: with neck cooling (COOL) and without neck cooling (CON). All participants completed both conditions, and the order of condition assignment was determined by a random draw. Participants first rested for 10 minutes in a 28.0 °C, 50% relative humidity environment, followed by a rest in a 35.0 °C, 50% relative humidity environment for another 10 minutes. In the COOL condition, participants wore a neck cooler containing 1,200 g of ice while exercising at 50% Heart Rate Reserve on a bicycle ergometer for 20 minutes. Afterward, they rested for 15 minutes in the hot environment while still wearing the cooler. Main outcome measures: Core body temperature (rectal and esophageal), forehead skin temperature, and heart rate were continuously monitored and compared using a mixed model. Estimated sweat volume was calculated based on changes in body weight before and after the experiment. Results: At the end of the rest period, no significant differences were observed between the COOL and CON conditions in rectal temperature (37.76 ± 0.18 °C versus 37.75 ± 0.24 °C, p = 0.9493), esophageal temperature (37.75 ± 0.30 °C versus 37.76 ± 0.23 °C, p = 0.7325), forehead skin temperature (36.87 ± 0.29 °C versus 36.88 ± 0.27 °C, p = 0.2160), or heart rate (104.18 ± 7.56 bpm versus 107.52 ± 7.40 bpm, p = 0.1035). Estimated sweat loss was similar between conditions (578 ± 175 g for CON versus 572 ± 242 g for COOL, p = 0.5066). While more participants felt cooler in the COOL condition, RPE showed no significant difference. Conclusion: Neck cooling did not significantly affect core temperature or perceived exertion. Maintaining close contact with the skin at sufficiently low temperatures or utilizing cooling methods that prevent excessive negative feedback may be necessary to enhance the effectiveness of neck cooling.